Implementation of Bilingual Learning: Perspectives, Challenges, and Obstacles - Thursina Andayani; M. Syukri Pesillete; Wulan Widiya Rahayu (Program Pendidikan Bahasa Inggris Universitas Tridinanti, 2024)
Bilingual learning programs refer to two-language learning programs that use the mother tongue and foreign language as learning media. Palembang Civil Aviation Polytechnic has implemented a bilingual learning program based on the curriculum issued by the Human Resources and Development Agency of the Ministry of Transportation. This research aimed to assess the degree of success of bilingual implementation in Polytechnic Civil Aviation Polytechnic. This research used a descriptive qualitative approach, where observation and interview were used to collect data involving all lecturers and cadets using intact sampling with 297 (12 lecturers and 286 cadets). Thematic analysis was used to analyze the data. The data result showed that lecturers and cadets have positive perspectives on bilingual learning even though improvements need to be made to implement bilingual learning to be more effective. In the implementation of bilingual learning, it was indicated that there were some issues regarding challenges and obstacles during bilingual learning. In the challenges, it was found that the participants were not motivated to speak English and were confused about the English language applied in the field of aviation and the goal of the bilingual learning program. Moreover, the lecturers and cadets faced obstacles dealing with material sources, infrastructure support, attitude, ability, and English proficiency.